Sinergi Olahraga, Pariwisata, dan Kebudayaan sebagai Penggerak Ekonomi Daerah Kabupaten Serdang Bedagai - Aldhila, Adang (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2026)
This study aims to analyze the potential, constraints, and synergy strategies between the sports, tourism, and culture sectors as drivers of the regional economy in Serdang Bedagai Regency. The research background is based on the large potential of natural resources, the richness of multi-ethnic culture, and the increasing trend of community sports that can be integrated into the regional development framework. However, the utilization of this potential still faces various obstacles, such as institutional fragmentation, limited infrastructure, suboptimal promotion, unequal community capacity, and limited regional budgets amidst national fiscal efficiency policies. This study uses a qualitative method with a literature review approach to examine concepts, theories, and empirical findings relevant to the development of sports tourism, community-based tourism, collaborative governance, and sustainable development. The results of the study indicate that the integration of the sports, tourism, and culture sectors has the potential to create an economic multiplier effect through increased tourist visits, development of MSMEs, job creation, and increased Regional Original Income (PAD). Recommended strategies include the development of an integrated event calendar, development of local culture-based sports tourism, strengthening branding and digital marketing, implementing public-private partnerships, increasing community capacity, innovation of thematic tour packages, development of integrated facilities, and a monitoring and evaluation system based on performance indicators. With a collaborative governance approach and integrated planning, the synergy of sports, tourism, and culture is expected to be a resource efficiency strategy as well as a driving force for inclusive, competitive, and sustainable economic growth in Serdang Bedagai Regency.